Primulina clausa, a new species of Gesneriaceae from northern Guangxi, China - Li, Peng-Wei; Pan, Bo; Harris, Aj; Xu, Wei-Bin; Liu, Ming-Tao; Kang, Ming (Phytotaxa, 2021)
A new species of Gesneriaceae, Primulina clausa P.W.Li & M.Kang was described, which occurs in the karst areas of northern Guangxi Zhuang Autonomous Region of China. The new species is morphologically similar to P. obtusidentata (W.T.Wang) Mich.Möller & A.Weber, but can be readily distinguished by its short and prostrate peduncle, slightly unfolded bracts, appressed sepals, glabrous anthers, parietal placenta, and nearly straight capsules.